Biophilic architecture and spatial perception: the case of Geoffrey Bawa’s key works and the PAM centre, a comparative analysis / Ahmad Zharif Ahmad Zahir and Farah Shahira Azmi - Ahmad Zahir, Ahmad Zharif; Azmi, Farah Shahira (Universiti Teknologi MARA, Perak, 2024)
The three main design parameters noted in the applications of biophilic architecture, Nature in the Space, Natural Analogues, and Nature of the Space are key design principles that focus on the integral relationship between the natural and the built environment. This study explores the application of these primary Biophilic design principles in Geoffrey Bawa’s architecture focusing on the indispensable aspects of both; architectural design (the craft) and user experience (the psychological and the social well-being), measured through aspect of spatial perception. As this study aims to benefit the discourse of Malaysian Architecture, it will bring forth the corollaries between Geoffrey Bawa’s architecture and the newly retrofitted Centre of Malaysian Institute of Architects (PAM). Geoffrey Bawa is noted as the internationally recognised leading architect practicing Biophilic design. In this research there are three key questions that have been addressed; (1) What roles do these three primary Biophilic design principles play in architecture? (2) How do they then engender a concrete sense of a cohesive and natural-feeling environment to the general user in the PAM Centre? (3) How effective is the Biophilic design applied in the PAM Centre in nurturing close-knit connection with Nature for its users, compared to other architecture of equivalent typology, namely public building. This study is driven by qualitative methodologies, covering document analysis, precedent study, and a comprehensive case study of the PAM Centre. This case study involves a comparative analysis of the Biophilic design principles specifically drawn from architectures of Geoffrey Bawa and their applications in the PAM Centre. The findings reveal a deep understanding of three (3) main pillars of the Biophilic design and their effective integration as already manifested by Geoffrey Bawa, which enhances the natural ambiance and connectivity to nature within building and built environment. In conclusion, the research demonstrates Bawa’s Biophilic design principles which is evident in the architecture of PAM Centre successfully creating environments that are both natural and supportive of human well-being.